Measurement of the B -> Dl nu branching fractions and form factor - Bartelt, J; Csorna, SE; McLean, K; Marka, S; Xu, Z; Godang, R; Kinoshita, K; Lai, I; Pomianowski, P; Schrenk, S; Bonvicini, G; Cinabro, D; et al. (1999)
Using a sample of 3.3 × 106 B-meson decays collected with the CLEO detector at the Cornell Electron Storage Ring, we have studied B → D0ℓ ν̄ and B̄0 → D ℓ ν̄ decays, where ℓ can be either e- or μ-. We distinguish B → Dℓν from other B semileptonic decays by examining the net momentum and energy of the particles recoiling against D - ℓ pairs. We find Γ(B → Dℓν) = (14.1 ± 1.0 ± 1.2) ns-1 and derive branching fractions for B- → D0ℓ- ν̄ and B̄0 → D+ℓ- ν̄ of (2.32 ± 0.17 ± 0.20)% and (2.20 ± 0.16 ± 0.19)%, respectively, where the uncertainties are statistical and systematic. We also investigate the B → Dℓν form factor and the implication of the result for |Vcb|. © 1999 The American Physical Society.